Retention efficiencies of halogenated and non-halogenated hydrocarbons in selected wetland ecosystem in Lake Victoria Basin - Mule, Shadrack; Nguta, Charles; Kamau, Geoffrey; Ongera, Gilbert; Wangila, Phanice; Kiplimo, Joyce; Chirchir, Dennis (International Journal of Environment, 2015)
The determination of retention efficiencies of halogenated and non-halogenated hydrocarbon in selected wetland ecosystems in Lake Victoria basin was carried out. Qualitative and quantitative determination of the presence of residual hydrocarbons in Kigwal/Kimondi, Nyando and Nzoia wetland ecosystems using Gas Chromatography - Mass Spectrometer (GC-MS) instrument indicated the presence of residual organochlorines, organophosphorus, carbamates and synthetic pyrethroid hydrocarbons in water, sediment and plant materials. In order to compare the retention efficiencies of the wetlands, the wetland ecosystems were divided into three different sections, namely: inlet, mid and outlet. Calculations of mass balances of residual halogenated and non-halogenated hydrocarbons at the respective sections was done taking into account the partition of the studied compounds in samples of water, sediments and papyrus reed plant materials and analyzed using validated Gas Chromatography - Mass Spectrometer (GC-MS) method. From the analysis, several residual hydrocarbons namely: bendiocarb, benzene hexachloride (BHC), carbaryl, cypermethrin, decis, deltamethrin, diazinon, dieldrin, DDT, DDD, DDE, malathion, propoxur, sumithion, 5-phenylrhodanine, 1,3,5-trichlorobenzene, 1-(2-phenoxybenzyl)hydrazine were detected and quantified. The levels of the selected residual hydrocarbons in water samples were used to calculate the retention efficiencies of a specific hydrocarbon and the values recorded. Generally, River Nyando wetland recorded mean percentage retention efficiencies of 76 and 94% for dry and rainy seasons respectively; Kigwal/Kimondi wetland had seasonal mean percentage retention efficiencies of 63 to 78%. River Nzoia also had calculated seasonal mean percentage retention efficiencies of between 56 to 88%. Dry season had lower mean percentages retention efficiencies as compared to rainy season in the three wetlands of interest during the period of study. The study observed that retention efficiencies of tropical wetland ecosystems is greatly affected by its concentration within the wetland tank systems, anthropogenic activities, physical properties of the hydrocarbon, and environmental conditions among others. There are several anthropogenic activities which contributed to the presence of hydrocarbons in the wetlands and they included: agricultural, municipal, industrial and public health activities. DOI: http://dx.doi.org/10.3126/ije.v4i2.12623 International Journal of Environment Vol.4(2) 2015: 38-52